High-performance soft magnetic composite material and preparation method thereof

High-performance soft magnetic composite materials were prepared by arranging filamentous soft magnetic alloys in parallel along the working magnetic circuit direction and filling the non-working magnetic circuit direction with an insulating medium. This solved the bottleneck problems of magnetic permeability and loss in traditional materials and achieved high-performance optimization of the materials.

CN120878385APending Publication Date: 2025-10-31CHINA JILIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511272560.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Traditional soft magnetic composite materials provide high permeability and low loss in the working magnetic circuit direction, but fail to effectively provide high impedance in the non-working magnetic circuit direction, resulting in the failure to maximize the performance of the material components.

Method used

High-performance soft magnetic composite materials are prepared by arranging filamentous soft magnetic alloys in parallel and orderly manner in the working magnetic circuit direction and filling them with a high resistivity insulating medium in the non-working magnetic circuit direction.

Benefits of technology

It effectively reduces the magnetic resistance of the working magnetic circuit, increases the permeability and reduces the loss, breaks through the bottleneck of permeability and high-frequency loss of traditional soft magnetic composite materials, and promotes the miniaturization and high-frequency operation of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120878385A_ABST
    Figure CN120878385A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance soft magnetic composite material and a preparation method thereof, and belongs to the technical field of preparation of soft magnetic composites.The preparation method of the high-performance soft magnetic composite material comprises the following steps that filamentous soft magnetic alloy is arranged in parallel and in order in the working magnetic circuit direction (the annular direction), and is filled with insulating media in the non-working magnetic circuit direction (the axial direction and the radial direction); and preparing to obtain the high-performance soft magnetic composite material. The soft magnetic composite material prepared by the preparation method provided by the invention has the following three advantages: (1) magnetic resistance is reduced; and an insulating air gap in the working magnetic circuit direction is eliminated, so that the magnetic resistance is reduced to 1 / 10 of that of a traditional structure, and the magnetic conductivity is greatly improved. And (2) eliminating a demagnetizing field. The axial demagnetization factor N of the filiform structure is equal to 0, and compared with spherical particles (N is equal to 1 / 3), the local demagnetization field is remarkably reduced, so that the magnetic conductivity is improved, and the magnetic hysteresis loss is reduced. And (3) the performance of the material components is utilized to the maximum extent. The induced eddy current is perpendicular to the magnetic circuit, and the size of the induced eddy current is directly related to the resistivity in the direction perpendicular to the magnetic circuit but not related to the resistivity in the magnetic circuit direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of soft magnetic composite material preparation technology, and particularly relates to a high-performance soft magnetic composite material and its preparation method. Background Technology

[0002] Soft magnetic materials, as the core medium for achieving magnetoelectric energy conversion, hold an irreplaceable strategic position in fields such as power transmission, information communication, and new energy equipment. Their performance directly determines the energy conversion efficiency and power density of electrical equipment. With the evolution of power electronic equipment towards miniaturization, high frequency, and intelligence, soft magnetic materials are also rapidly developing towards high permeability, high frequency, and low loss. Soft magnetic materials mainly include metallic soft magnetic materials, ferrite soft magnetic materials, and soft magnetic composite materials. Metallic soft magnetic materials meet the requirements of equipment miniaturization with their high saturation magnetic flux density (Bs≈2.0T); however, their low resistivity leads to an exponential increase in high-frequency eddy current losses, which limits the application of these materials in high-frequency fields. Ferrite soft magnetic materials, with their high resistivity and excellent high-frequency characteristics, perform well in the MHz to GHz high-frequency range; however, limited by subferromagnetism, their saturation magnetic flux density is generally below 0.5T, severely restricting the improvement of energy density. Soft magnetic composite materials combine the advantages of metallic soft magnetic materials and ferrite soft magnetic materials, constructing a composite structure of "metallic core + insulating medium": the main phase is a soft magnetic alloy with high saturation magnetic flux and high energy density; the interface is an insulating medium with high resistivity and low high-frequency eddy current loss. This unique structure enables soft magnetic composite materials to simultaneously achieve high magnetic flux and low loss, thus meeting the miniaturization and high-frequency application requirements of devices in the kHz to MHz range. With the booming development of new energy industries represented by wind power, 5G communication, and electric vehicles, the research and application of soft magnetic composite materials have ushered in unprecedented opportunities and challenges.

[0003] In recent years, academia and industry have mainly focused on three aspects of research: composition design, interface engineering, and process innovation. In terms of composition design, researchers have used multi-element alloying to control properties such as permeability, resistivity, and losses. For example, the team led by Dong Yaqiang at the Chinese Academy of Sciences (Z.Liu, Y.Dong, X.Liu, H.Lu, Y.Wu, H.Zhang, A.He, J.Li, X.Wang, Microstructure and soft magnetic properties of Fe) 85-x Si 9.6 Al 5.4 Ti x (Composite magnetic powder cores, J. Alloy. Compd., 885(2021)160924.) Introducing Ti into FeSiAl reduces the loss to 140.6 mW / cm at 1 MHz. 3The team led by Wang Dezhi at Central South University (Le Chen. Preparation and performance study of Co-doped Fe-6.5wt%Si magnetic powder core [D]. Central South University, 2014) increased the saturation magnetization of FeSi alloy to 219.26 emu / g through Co doping; Interface engineering is a research hotspot, focusing on improving the insulation properties and magnetic properties of the interface. The team led by Zhu Zhenghou at Nanchang University (Zeng Chaochao. Study on microstructure and soft magnetic properties of FeSiY alloy magnetic powder core [D]. Nanchang University, 2022) utilized SiO2 to coat Fe 93.5 Si 4.3 Y 2.2 The alloy achieved an effective magnetic permeability of 67 at 10 kHz. The team led by Yan Mi at Zhejiang University (W. Wan, C. Wu, G. Liu, Q. Chen, M. Yan, High-performance CeFeCo / FeSiAl soft magnetic composites for megahertz power devices, AIP Adv., 14(2024)055213.) prepared CeFeCo / FeSiAl@PU SMCs by hot pressing, exhibiting a relative magnetic permeability of 21.0 and a maximum power of 3677.5 kW·m at 5 MHz. -3 Power loss; process innovation is achieved by integrating new processes and optimizing the microstructure to improve soft magnetic properties. The team led by Zhao Zhankui at Changchun University of Technology (Z. Zhao, Y. Sun, M. Wang, Y. Chi, H. Wang, Interfacial behavior of Fe) 76 Si9B 10 P5 / Zn 0.5 Ni 0.5 (Fe2O4 amorphous soft magnetic composite during spark plasma sintering process, Prog. Nat. Sci.-Mater., 26(2023) 85-89.) A layered oriented amorphous soft magnetic composite material was prepared using SPS sintering technology to achieve the goal of high magnetic permeability in the magnetic circuit direction.

[0004] Despite the significant progress made in the above studies, the "isotropic core-shell structure" of traditional soft magnetic composite materials (Y.Xu,C.Zhang,X.Peng,J.Li,S.Tao,Q.Wu,J.Xu,B.Hong,X.Wang,H.Ge,Design,fabrication,andmagneticpropertiesofiron-based soft magnetic composites with La2NiMnO6 ferromagneticinsulation layer,Ceram Int,49(2023)40347-40357.) still has intrinsic defects.

[0005] Therefore, there is an urgent need to provide an ideal soft magnetic composite material that can provide high permeability and low loss in the working magnetic circuit direction, and high impedance in the non-working magnetic circuit direction, so as to maximize the role of each component. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention proposes a high-performance soft magnetic composite material and its preparation method.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] A method for preparing a high-performance soft magnetic composite material includes the following steps:

[0009] The high-performance soft magnetic composite material is prepared by arranging filamentous soft magnetic alloys in parallel and orderly in the working magnetic circuit direction and filling the non-working magnetic circuit direction with an insulating medium.

[0010] Optionally, the working magnetic circuit direction is circumferential, and the non-working magnetic circuit direction is axial and radial.

[0011] Optionally, the filamentous soft magnetic alloy is selected from any one of iron-silicon alloy, iron-nickel alloy, iron-aluminum alloy, iron-cobalt alloy, iron-silicon-chromium alloy, iron-silicon-aluminum alloy, iron-nickel-copper alloy, and iron-nickel-molybdenum alloy, and its diameter (wire diameter) is 0.01-0.3 mm.

[0012] Furthermore, the diameter of the filamentous soft magnetic alloy is 0.05, 0.10, 0.15, 0.20, 0.25 or 0.30 mm.

[0013] Optionally, the insulating medium is at least one selected from acrylic resin, silicone resin, epoxy resin, silica, alumina, and kaolin.

[0014] Optionally, the preparation method of the high-performance soft magnetic composite material specifically includes the following steps:

[0015] The filamentous soft magnetic alloy was pretreated by sequentially immersing it in degreasing solution, pickling solution, and passivation solution; then it was washed with water and dried.

[0016] The pretreated filamentous soft magnetic alloy is immersed in an insulating medium, then cured, and then coated with insulation.

[0017] The soft magnetic alloy wires, which have been insulated and coated, are arranged in a parallel and orderly manner along the working magnetic circuit (circumferential direction) and wound into a magnetic ring;

[0018] The magnetic ring is immersed in an insulating medium to coat its surface with an organic insulating layer.

[0019] Furthermore, the degreasing solution is acetone or ethanol.

[0020] Furthermore, the pickling solution is HCl or H2SO4 with a volume concentration of 5%-10%, and the pickling time is 1-2 minutes.

[0021] Furthermore, the passivation solution is H3PO4 or HNO3 with a volume concentration of 20%.

[0022] Furthermore, the passivation time during the passivation process is 5-10 minutes, and the passivation temperature is 60-95℃.

[0023] Furthermore, the curing is performed by ultraviolet curing or heat curing.

[0024] Furthermore, the UV curing time is 1-30 seconds.

[0025] A high-performance soft magnetic composite material is prepared by the above-described preparation method.

[0026] Optionally, the high-performance soft magnetic composite material includes a soft magnetic alloy core and an insulating medium, specifically, the soft magnetic alloy is arranged in an orderly manner and the insulating medium fills the gaps between them.

[0027] Compared with the prior art, the present invention has the following advantages and technical effects:

[0028] 1. The soft magnetic composite material prepared by this invention has a novel structural design and a breakthrough parallel ordered structure design of filamentous soft magnetic alloy, which effectively reduces the magnetic resistance of the working magnetic circuit and provides a new idea for the design of high-performance soft magnetic materials.

[0029] 2. By optimizing the preparation process and the filling of the insulating medium, the synergistic optimization of structure and magnetism is achieved.

[0030] 3. This invention effectively reduces the magnetic resistance of the working magnetic circuit, effectively improves the permeability of the soft magnetic composite material and reduces the loss, breaks through the bottleneck of traditional soft magnetic composite materials in terms of permeability and high-frequency loss, and promotes the miniaturization and high-frequency operation of soft magnetic composite materials.

[0031] 4. Maximizing the utilization of material component properties: Induced eddy currents are perpendicular to the magnetic circuit, and their magnitude is directly related to the resistivity in the direction perpendicular to the magnetic circuit, but independent of the resistivity in the direction of the magnetic circuit. Attached Figure Description

[0032] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0033] Figure 1 This is a schematic diagram of the structure of the magnetic ring formed by arranging the filamentous soft magnetic alloy in parallel and orderly along the working magnetic circuit (circumferential direction) according to the present invention;

[0034] Figure 2 This is a graph showing the permeability data of the magnetic ring fabricated in Example 1;

[0035] Figure 3 This is a graph showing the permeability data of the magnetic ring fabricated in Example 2;

[0036] Figure 4 This is a graph showing the permeability data of the magnetic ring fabricated in Example 3;

[0037] Figure 5 This is a graph showing the permeability data of the magnetic ring fabricated in Example 4;

[0038] Figure 6 This is a graph showing the permeability data of the magnetic ring fabricated in Example 5;

[0039] Figure 7 This is a graph showing the permeability data of the magnetic ring fabricated in Example 6;

[0040] Figure 8 This is a graph showing the permeability data of the magnetic ring fabricated in Example 7;

[0041] Figure 9 This is a graph showing the magnetic loss data of the magnetic ring fabricated in Example 1;

[0042] Figure 10 This is a graph showing the magnetic loss data of the magnetic ring fabricated in Example 2;

[0043] Figure 11 This is a graph showing the magnetic loss data of the magnetic ring fabricated in Example 3;

[0044] Figure 12 This is a graph showing the magnetic loss data of the magnetic ring fabricated in Example 4;

[0045] Figure 13 This is a graph showing the magnetic loss data of the magnetic ring fabricated in Example 5;

[0046] Figure 14 This is a graph showing the magnetic loss data of the magnetic ring fabricated in Example 6;

[0047] Figure 15 This is a graph showing the magnetic loss data of the magnetic ring fabricated in Example 7;

[0048] Figure 16 This is a schematic diagram of the structure of a traditional soft magnetic composite material, as shown in Comparative Example 1.

[0049] Figure 17 (a) is a comparison diagram of the magnetic properties of the soft magnetic composite material prepared in Example 1 of the present invention and the traditional soft magnetic composite material in Comparative Example 1; (b) is a comparison diagram of the magnetic properties of the soft magnetic composite material prepared in Example 1 of the present invention and various commercial magnetic cores. Detailed Implementation

[0050] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0051] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0052] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0053] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0054] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0055] This invention provides a method for preparing high-performance soft magnetic composite materials. By arranging filamentous soft magnetic alloys in parallel and orderly manner in the working magnetic circuit (circumferential direction), and filling the non-working magnetic circuit directions (axial and radial directions) with high resistivity insulating media (such as acrylic resin, epoxy resin, organosilicon resin, alumina / silica / kaolin, phosphate passivation film, nitrate passivation film, etc.), its advantages are reduced magnetic resistance, elimination of demagnetizing field and maximization of the performance of material components.

[0056] This invention discloses a high-performance soft magnetic composite material, comprising a metal (soft magnetic alloy) core and an insulating medium; its preparation process is as follows:

[0057] (1) Degreasing: Immerse the soft magnetic alloy wire in degreasing solution to remove the oil residue on the surface during processing, and then clean it with deionized water;

[0058] (2) Remove oxide film: Immerse the soft magnetic alloy wire in pickling solution, and immediately rinse with deionized water after pickling to remove acid;

[0059] (3) Surface passivation: The soft magnetic alloy wire is immersed in the prepared passivation solution to form a passivation film on the surface of the soft magnetic alloy wire and perform online surface passivation treatment.

[0060] (4) Washing and drying: After passivation, the soft magnetic alloy wire is immersed in deionized water to remove the residual passivation solution, and then the surface is dried to remove the residual moisture.

[0061] (5) Insulation coating: The passivated soft magnetic alloy wire is then uniformly immersed in the insulating medium;

[0062] (6) Insulation layer curing: The soft magnetic alloy wire is cured by ultraviolet curing equipment or by heating to form a dense organic insulation layer on its surface.

[0063] (7) Magnetic ring winding: The treated soft magnetic alloy wire is wound into a magnetic ring by arranging the wires in parallel and orderly along the working magnetic circuit (circumferential direction);

[0064] (8) Post-processing: Immerse the wound magnetic ring in the insulating medium to coat its surface with an organic insulating layer.

[0065] In some optional embodiments, the soft magnetic alloy wire used is at least one of the following: iron-silicon alloy, iron-nickel alloy, iron-aluminum alloy, iron-cobalt alloy, iron-silicon-chromium alloy, iron-silicon-aluminum alloy, iron-nickel-copper alloy, and iron-nickel-molybdenum alloy, and the wire diameter of the soft magnetic alloy wire is 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, or 0.30 mm.

[0066] In some alternative embodiments, in step (1), the degreasing agent is acetone or ethanol.

[0067] In some alternative embodiments, in step (2), the pickling solution is HCl or H2SO4 with a volume concentration of 5%-10%, and the pickling time is 1-2 min.

[0068] In some alternative embodiments, in step (3), the passivation solution is H3PO4 or nitric acid with a volume concentration of 20%, the passivation time is 5-10 min, and the passivation temperature is 60-90℃.

[0069] In some alternative embodiments, in steps (5) and (8), the insulating medium is acrylic resin (wherein the content of acrylic monomer is 30wt%-50wt%), silicone resin, epoxy resin, silica, alumina or kaolin.

[0070] In some alternative embodiments, in step (6), the duration of ultraviolet irradiation is 1-30 seconds.

[0071] Unless otherwise specified, the term "parts" in this invention refers to parts by weight.

[0072] All raw materials used in this invention were purchased commercially. The acrylic resin was purchased from Chongqing Siling Technology Co., Ltd., model GN3210 ultra-rare; the epoxy resin was purchased from Huizhou Sanhua Electronic Insulation Materials Co., Ltd., model AG-80; the silicone resin was purchased from Wanhua Chemical Co., Ltd., model SES-1012; the kaolin powder was purchased from Lingshou Pengyi Mineral Products Processing Plant, model 0810; and the photosensitive adhesive was purchased from Youming Chemical Co., Ltd., model T20D.

[0073] The technical solution of the present invention will be further illustrated by the following embodiments.

[0074] Example 1

[0075] A method for preparing a high-performance soft magnetic composite material includes the following steps:

[0076] Iron-nickel-molybdenum wire alloy with a diameter of 0.10 mm was selected, cleaned with ethanol, rinsed with deionized water, acid-washed in 10% HCl solution, and then immersed in H3PO4 solution with a volume concentration of 20% for passivation at a passivation temperature of 90℃ for 5 min. The passivated soft magnetic alloy wire was then immersed in deionized water to remove the residual passivation solution, and then the surface was dried to remove residual moisture.

[0077] Add 15 wt.% silica powder (15 wt.% is the mass percentage of silica in acrylic resin, the same below) to acrylic resin and stir to make it evenly distributed in acrylic resin; then immerse the iron-nickel-molybdenum wire alloy into the prepared acrylic resin-silica powder mixture; then cure it by irradiation with ultraviolet curing equipment for 15 seconds.

[0078] Iron-nickel-molybdenum wire alloy is wound into a magnetic ring by arranging the wires in a parallel and orderly manner along the working magnetic circuit (circumferential direction);

[0079] The wound magnetic ring is immersed in epoxy resin, so that its surface is covered with an organic insulating layer.

[0080] The permeability and magnetic loss of the soft magnetic composite material prepared in Example 1 are as follows: Figure 2 and Figure 9 As shown in the figure, compared with the same specification magnetic powder core (purchased from Shantou Shihe Magnetic Materials Electronics Factory, model NPF080090), it exhibits superior magnetic properties. Furthermore, the magnetic loss of the soft magnetic composite material prepared in Example 1 is reduced by ten times compared to other examples, resulting in a significant improvement in magnetic properties.

[0081] Example 2

[0082] A method for preparing a high-performance soft magnetic composite material includes the following steps:

[0083] Iron-silicon-aluminum wire alloy with a diameter of 0.30 mm was selected, cleaned with ethanol, rinsed with deionized water, acid-washed in 10% HCl solution, and then passedivated by immersing in 20% H3PO4 solution at a passivation temperature of 90℃ for 5 min. After passivation, the soft magnetic alloy wire was cleaned with deionized water and then dried.

[0084] Add 5 wt.% alumina powder to acrylic resin and stir to distribute it evenly in the acrylic resin; then immerse the iron-silicon-alumina wire alloy into the prepared acrylic resin-alumina powder mixture solution to evenly coat it with a layer of acrylic resin, and then cure it by ultraviolet irradiation for 30 seconds.

[0085] The processed iron-silicon-aluminum wire alloy is arranged in a parallel and orderly manner along the working magnetic circuit (circumferential direction) and wound into a magnetic ring;

[0086] The wound magnetic ring is immersed in silicone resin, so that its surface is coated with an organic insulating layer.

[0087] The permeability and magnetic loss of the soft magnetic composite material prepared in Example 2 are as follows: Figure 3 and Figure 10 As shown.

[0088] Example 3

[0089] A method for preparing a high-performance soft magnetic composite material includes the following steps:

[0090] Iron-nickel-copper wire alloy with a diameter of 0.20 mm was selected, cleaned with acetone, rinsed with deionized water, acid-washed in 10% HCl solution, and then passedivated by immersion in 20% HNO3 solution at a passivation temperature of 60℃ for 10 min; after cleaning the surface with deionized water, it was dried.

[0091] Add 5 wt.% silica powder to acrylic resin and stir to distribute it evenly in the acrylic resin; then immerse the iron-nickel-copper wire alloy into the prepared acrylic resin-silica powder mixture solution to evenly coat it with a layer of acrylic resin, and then cure it by ultraviolet irradiation for 10 seconds.

[0092] The processed iron-nickel-copper wire alloy is arranged in a parallel and orderly manner along the working magnetic circuit (circumferential direction) and wound into a magnetic ring;

[0093] The wound magnetic ring is immersed in acrylic resin, which coats its surface with an organic insulating layer.

[0094] The permeability and magnetic loss of the soft magnetic composite material prepared in Example 3 are as follows: Figure 4 and Figure 11 As shown.

[0095] Example 4

[0096] A method for preparing a high-performance soft magnetic composite material includes the following steps:

[0097] Select iron-silicon-aluminum wire alloy with a diameter of 0.05 mm, clean it with ethanol, rinse it with deionized water, pickle it in 10% HCl solution, and then immerse it in 20% H3PO4 solution for passivation at a passivation temperature of 90℃ for 5 min. Then immerse the passivated soft magnetic alloy wire in deionized water to remove the residual passivation solution, and then dry the surface to remove residual moisture.

[0098] Add 10 wt.% kaolin powder to acrylic resin and stir to distribute it evenly in the acrylic resin; then immerse the iron-silicon-aluminum wire alloy into the prepared acrylic resin-kaolin powder mixture; then cure it by irradiation with ultraviolet curing equipment for 10 seconds.

[0099] Iron-silicon-aluminum wire alloy is wound into a magnetic ring by arranging the wires in a parallel and orderly manner along the working magnetic circuit (circumferential direction);

[0100] The wound magnetic ring is immersed in epoxy resin, so that its surface is covered with an organic insulating layer.

[0101] The permeability and magnetic loss of the soft magnetic composite material prepared in Example 4 are as follows: Figure 5 and Figure 12 As shown.

[0102] Example 5

[0103] A method for preparing a high-performance soft magnetic composite material includes the following steps:

[0104] Select an iron-aluminum wire alloy with a diameter of 0.01 mm, clean it with ethanol, rinse it with deionized water, then pickle it in 10% HCl solution, and then immerse it in 20% H3PO4 solution for passivation at a passivation temperature of 90℃ for 5 min. Then immerse the passivated soft magnetic alloy wire in deionized water to remove the residual passivation solution, and then dry the surface to remove residual moisture.

[0105] The iron-aluminum wire alloy is immersed in acrylic resin containing photosensitive adhesive (the amount of photosensitive adhesive added is 20 wt.% of the acrylic resin) to uniformly coat it with a layer of acrylic resin, and then cured by ultraviolet irradiation for 10 seconds.

[0106] The processed iron-aluminum wire alloy is arranged in a parallel and orderly manner along the working magnetic circuit (circumferential direction) and wound into a magnetic ring;

[0107] The wound magnetic ring is immersed in epoxy resin, so that its surface is covered with an organic insulating layer.

[0108] The permeability and magnetic loss of the soft magnetic composite material prepared in Example 5 are as follows: Figure 6 and Figure 13 As shown.

[0109] Example 6

[0110] A method for preparing a high-performance soft magnetic composite material includes the following steps:

[0111] Iron-silicon wire alloy with a diameter of 0.15 mm was selected, cleaned with acetone, rinsed with deionized water, then acid-washed in 10% H2SO4 solution, and then passedivated by immersing in 20% H3PO4 solution at a passivation temperature of 95℃ for 10 min. After cleaning the surface with deionized water, it was dried.

[0112] Add 10 wt.% alumina powder to acrylic resin and stir to distribute it evenly in the acrylic resin; then immerse the iron-silicon wire alloy into the prepared acrylic resin-alumina powder mixture; then cure it by irradiation with a UV curing device for 25 seconds.

[0113] The processed iron-silicon wire alloy is arranged in a parallel and orderly manner along the working magnetic circuit (circumferential direction) and wound into a magnetic ring;

[0114] The wound magnetic ring is immersed in epoxy resin, so that its surface is covered with an organic insulating layer.

[0115] The permeability and magnetic loss of the soft magnetic composite material prepared in Example 6 are as follows: Figure 7 and Figure 14 As shown.

[0116] Example 7

[0117] A method for preparing a high-performance soft magnetic composite material includes the following steps:

[0118] Select iron-cobalt wire alloy with a diameter of 0.05 mm, clean it with ethanol, rinse it with deionized water, pickle it in 10% HCl solution, and then immerse it in 20% H3PO4 solution for passivation at a passivation temperature of 90℃ for 5 min. Then immerse the passivated soft magnetic alloy wire in deionized water to remove the residual passivation solution, and then dry the surface to remove residual moisture.

[0119] Add 5 wt.% alumina powder to acrylic resin and stir to distribute it evenly in the acrylic resin; then immerse the iron-silicon-copper wire alloy into the prepared acrylic resin-alumina powder mixture solution to evenly coat it with a layer of acrylic resin, and then cure it by ultraviolet irradiation for 5 seconds.

[0120] The processed iron-cobalt wire alloy is arranged in a parallel and orderly manner along the working magnetic circuit (circumferential direction) and wound into a magnetic ring;

[0121] The wound magnetic ring is immersed in epoxy resin, so that its surface is covered with an organic insulating layer.

[0122] The permeability and magnetic loss of the soft magnetic composite material prepared in Example 7 are as follows: Figure 8 and Figure 15 As shown.

[0123] Comparative Example 1

[0124] Traditional soft magnetic composite materials (traditional isotropic FeNi magnetic core, which is also the traditional soft magnetic composite material in the background technology).

[0125] Figure 16 This is a schematic diagram of a traditional soft magnetic composite material, as shown in Comparative Example 1. Based on Ohm's law for magnetic circuits, the non-magnetic insulating layer forms a high reluctance air gap in the working magnetic circuit direction, leading to a decrease in the effective permeability of the magnetic core. Theoretical calculations show that even if the insulating medium (i.e., the air gap) occupies only 1% of the particle radius, the magnetic reluctance of the magnetic circuit increases by an order of magnitude, which causes the permeability of the magnetic core to decrease by an order of magnitude simultaneously. Secondly, the high demagnetization factor (N = 1 / 3) of spherical particles generates a high demagnetization field (Hd = -NMs), which not only suppresses the effective permeability but also significantly increases hysteresis loss. Furthermore, the traditional isotropic structure fails to fully utilize the magnetic components, only utilizing the magnetism in a single working magnetic circuit direction, while the excellent axial and radial magnetism is never utilized, resulting in a waste of approximately 67% of the magnetic energy.

[0126] Among them, the magnetic reluctance of the magnetic circuit (R) m The formula for calculating ) is:

[0127] R m =l core / μ0μ mag S+l gap / μ0μ gap S, where μ mag >>μ gap’ μ gap ≈1;

[0128] In the above formula, R m For magnetic reluctance in the magnetic circuit, l core Let μ be the average flux length of the magnetic core, μ0 be the free permeability, and μ mag Let S be the permeability of the core material, and S be the effective cross-sectional area of ​​the core. gap μ is the actual length of the air gap. gap is the air gap permeability.

[0129] Comparative Example 2

[0130] Commercial magnetic cores (purchased from manufacturers such as...) Figure 17 (As shown).

[0131] Figure 17 (a) is a comparison diagram of the magnetic properties of the soft magnetic composite material prepared in Example 1 of the present invention and the conventional soft magnetic composite material in Comparative Example 1; (b) is a comparison diagram of the magnetic properties of the soft magnetic composite material prepared in Example 1 of the present invention and various commercial magnetic cores. As can be seen from the figures, compared with the conventional isotropic FeNi magnetic core, the anisotropic magnetic core exhibits a 4.96-fold increase in effective permeability at 10mT@10kHz, and a significant reduction in magnetic loss to 9%. Compared with commercial magnetic cores, the anisotropic magnetic core exhibits an effective permeability exceeding all other types by 3 to 6 times, and also has lower magnetic loss. Figure 17 (b) Therefore, the anisotropic structure of alloy wire oriented along the working magnetic circuit and selectively filled with insulating medium is an effective way to improve the permeability of the magnetic core and optimize high-frequency magnetic loss.

[0132] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance soft magnetic composite material, characterized in that, Includes the following steps: The high-performance soft magnetic composite material is prepared by arranging filamentous soft magnetic alloys in parallel and orderly in the working magnetic circuit direction and filling the non-working magnetic circuit direction with an insulating medium.

2. The method for preparing a high-performance soft magnetic composite material according to claim 1, characterized in that, The working magnetic circuit direction is circumferential, and the non-working magnetic circuit directions are axial and radial.

3. The method for preparing a high-performance soft magnetic composite material according to claim 1, characterized in that, The filamentary soft magnetic alloy is selected from any one of the following: iron-silicon alloy, iron-nickel alloy, iron-aluminum alloy, iron-cobalt alloy, iron-silicon-chromium alloy, iron-silicon-aluminum alloy, iron-nickel-copper alloy, and iron-nickel-molybdenum alloy.

4. The method for preparing a high-performance soft magnetic composite material according to claim 1, characterized in that, The insulating medium is at least one of acrylic resin, silicone resin, epoxy resin, silicon dioxide, alumina, and kaolin.

5. The method for preparing a high-performance soft magnetic composite material according to claim 1, characterized in that, Specifically, the following steps are included: The filamentous soft magnetic alloy was pretreated by sequentially immersing it in degreasing solution, pickling solution, and passivation solution; then it was washed with water and dried. The pretreated filamentous soft magnetic alloy is immersed in an insulating medium and then cured for insulation coating. The soft magnetic alloy wires, which have been insulated and coated, are arranged in a parallel and orderly manner along the working magnetic circuit and wound into a magnetic ring; The magnetic ring is immersed in an insulating medium to coat its surface with an insulating layer.

6. The method for preparing a high-performance soft magnetic composite material according to claim 5, characterized in that, The degreasing solution is acetone or ethanol; and / or, The pickling solution is HCl or H2SO4, with a concentration of 5 vol.% to 10 vol.%.

7. The method for preparing a high-performance soft magnetic composite material according to claim 5, characterized in that, The passivation solution is H3PO4 or HNO3, with a concentration of 20 vol.%.

8. The method for preparing a high-performance soft magnetic composite material according to claim 7, characterized in that, The passivation time during the passivation process is 5-10 minutes, and the passivation temperature is 60-95℃.

9. The method for preparing a high-performance soft magnetic composite material according to claim 5, characterized in that, The curing process is either ultraviolet curing or heat curing.

10. A high-performance soft magnetic composite material, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.